The Routledge encyclopedia of Mark Twain. - 4 0 16; (James Darrell), 1934- ,;1946- , LeMaster, J. R.,;Wilson, James D.;Hamric, Christie Graves; 5 (New York : Routledge, 2011)
Over 700 alphabetically arranged articles covering Mark Twain's life and career including entries on each of his works, his characters, personal influences, and longer articles on recurring themes or concepts in his works.
Includes bibliographical references and index.
Keywords: Encyclopedias. -- 2 -- Twain, Mark, -- 0 -- 1835-1910; 6; Authors, American;Authors, American -- 19th century -- Biography;Encyclopedias.;Biography;Encyclopedias.; 20; 2